Antinociceptive Effects of Valeriana Extract in Mice: Involvement of the Dopaminergic and Serotonergic Systems - Shahidi, S.; Bathaei, A.; Pahlevani, P. (Нейрофизиология, 2013)
Valeriana officinalis has been extensively used as a herbal remedy in traditional medicine. However, there is no clear evidence on the antinociceptive effects of this plant. The aim of our study was to evaluate the effect of Valeriana officinalis hydroalcoholic extract on pain modulation and its possible mechanism in mice. Adult male Balb/c mice were randomly divided into nine experimental groups. They received i.p. injections of saline, hydroalcoholic root extract of Valeriana officinalis (800, 200, or 50 mg/kg), and morphine; four groups received Valeriana (800 mg/kg) + antagonists of the systems involved in antinociception effects, naloxone, ondansetron, metoclopramide, or scopolamine. Tail-flick and writhing tests were used for estimation of possible modulation of pain. The tail-flick latencies in the Valeriana 800 and 200 mg/kg, but not 50 mg/kg, morphine, and combined Valeriana 800 + naloxone, ondansetron, metoclopramide, or scopolamine-treated groups were significantly longer than that in the control group. However, the tail-flick latencies in the Valeriana 800 mg/kg + ondansetron- and metoclopramide-treated groups were significantly shorter than that upon single action of the extract (800 mg/kg). The numbers of writhings in the extract-treated groups were smaller than in the control one. The numbers of writhings in the Valeriana (800 mg/kg)+ ondansetron- and metoclopramide-treated groups were significantly greater than in the extract (800 mg/kg) group. It is concluded that Valeriana officinalis extract possesses a clear analgesic effect and works through the serotonergic and dopaminergic systems.